American Indians Have a Higher Risk of Sjögren's Syndrome and More Disease Activity Than European Americans and African Americans. Issue 8 (5th July 2020) - Scofield, R. Hal; Sharma, Rohan; Pezant, Nathan; Kelly, Jennifer A.; Radfar, Lida; Lewis, David M.; Kaufman, C. Erick; Cioli, Sarah; Harris, Judy; Grundahl, Kiely; Rhodus, Nelson L.; Wallace, Daniel J.; et al.
Abstract : Objective: To describe the clinical and serologic manifestations of Sjögren's syndrome (SS) in ethnic groups of the US. Methods: This was a cross‐sectional study of 648 patients with primary SS: 20 African American (AA), 164 American Indian (AI), 426 European American (EA), and 38 patients of other races evaluated in a multidisciplinary Sjögren's International Collaborative Clinical Alliance research clinic. Results: AA subjects comprised 3.1% of the SS cohort, much lower than the percentage of AA in the state of Oklahoma ( P = 3.01 × E – 05), the US ( P = 2.24E – 13), or a systemic lupus erythematosus (SLE) cohort at the same institution ( P = 4.26 × 10E – 27). In contrast, the percentage of AI in the SS cohort (25.3%) was much higher than expected ( P = 3.17E – 09 versus SLE cohort, P = 6.36 – 26 versus Oklahoma, and P = 8.14E – 96 versus US population). The SS classification criteria were similar between AA and EA, but subjects of AI ancestry had lower rates of abnormal tear and salivary flow, as well as anti‐Ro/SSA and anti‐La/SSB antibodies. Paradoxically, AI had higher levels of disease activity (mean ± SD European League Against Rheumatism Sjögren's Syndrome Disease Activity Index score 3.77 ± 4.78) in comparison to EA (2.90 ± 4.12; P = 0.011) and more extraglandular manifestations affecting mainly the articular and glandular domains. Meanwhile, AA patients were characterized by higher rates of hypergammaglobulinemia (odds ratio [OR] 1.39 [95% confidence interval (95% CI) 1.39–8.65]; P = 0.01), elevated erythrocyte sedimentation rate (ESR) (OR 3.95 [95% CI 1.46–9.95]; P = 0.009), and parotid enlargement (OR 4.40 [95% CI 1.49–13.07]; P = 0.02). Conclusion: AI are affected at high rates with SS but present with few classical features, potentially preventing timely diagnosis. In contrast to SLE, SS is infrequent and not more severe among AA, but the triad of hypergammaglobulinemia, increased ESR, and parotid enlargement warrants extra vigilance for lymphomagenesis.